Estudo genético e citogenético de duas espécies do gênero Physalis (Solanaceae) - Araujo, Flaviane Leite (2012)
Noteworthy among the species included in the genus Physalis are P. angulata and P. peruviana because these species have medicinal and commercial potential, mainly due to the production of delicious fruits rich in vitamins A and C. In this work, we carried out a selection cycle of progenies of P. angulata, followed by evaluation and a study of genetic divergence, and also cytogenetic characterization of chromosomes of P. angulata and P. peruviana. We selected 45 progenies of P. angulata displaying the best means for the characters evaluated. The study of genetic divergence identified that the progenies possessed genetic variability, as evidenced by the formation of eight groups. The study allowed the indication of progenies for crossings which would result in good increase in fresh weight, plant height and fruit characters. In the study of chromosomal characterization it was found out that both P. angulata and P. peruviana display variations in number of chromosomes, with 44, 46 and 48 common to both species. P. angulata proved to be a polyploidy just like P peruviana. The chromosomes of P. angulata were classified as submetacentric, subtelocentric and metacentric and we suggest the following karyotypic formula for the species: 36SM+8ST+4M, with the submetacentric type being predominant. Therefore, we consider that there is crossing potential between the two species since the numbers and types of chromosomes are similar. Overall, the results of this study provide information that may aid breeding programs for improvement and hybridization of the species investigated.